Developing Capacity for the American Indian Health Professional Workforce: An Academic-Community Partnership in Spirit Lake, North Dakota - Jennifer Weintraub; Julia Walker; Loretta Heuer; Marisa Oishi; Khushbu Upadhyay; Vivian Huang; Cynthia Lindquist; Linda F. Cushman; Jonathan Ripp (Ubiquity Press, 2015)
Background: American Indians/Alaskan Native (AIAN) populations experience significant disparities in health when compared to the average US population who are under-represented in the health care professional workforce. Current research suggests that racial concordance between patients and providers has a positive effect on patient care. Objective: We describe a successful academic-community partnership between a tribal college, a local state academic center, an urban public health institution, and an urban academic center all aligned with the goal to increase AIAN health care professional capacity. Methods: A tribal college course and youth education program were developed with the intent to expose AIAN youth to the health care professions and encourage entry into health professional career tracks. Evaluation using a pre- and post-survey design is underway to assess the impact of the intervention on participating AIAN attitudes and career intentions. Conclusion: We believe this model is one way of addressing the need for an increased AIAN health care professional career force.